2011
DOI: 10.1590/s0100-83582011000400014
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and physiological alterations induced by lactofen in soybean leaves are reduced with nitric oxide

Abstract: Lactofen is a diphenylether herbicide recommended to control broad-leaved weeds in soybean (Glycine max) fields and its mechanism of action is the inhibition of protoporphyrinogen-IX oxidase (Protox), which acts in the chlorophyll biosynthesis. This inhibition results in an accumulation of protoporphyrin-IX, which leads to the production of reactive oxygen species (ROS) that cause oxidative stress. Consequently, spots, wrinkling and leaf burn may occur, resulting in a transitory crop growth interruption. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Treatments consisted of a combination of an aqueous solution of sodium nitroprusside (SNP, NO donor; Na 2 [Fe (CN) 5 NO]•2H 2 O, SigmaAldrich, Saint Louis, MO, USA) and elevated temperature imposed at the V3 development stage [17]. The plants were treated with two doses of SNP: 0 and 100 µM for two consecutive days at 24-h intervals, using a hand sprayer with a total volume of 5 mL per plant [18], under 25 • C and 40 • C. The high temperature (HT) was imposed after the both SNP applications by gradually increasing from 25 • C at 10:00 a.m. until reaching 40 • C ± 0.5 • C at 11:30 a.m., which was maintained for five hours. After this period, the temperature gradually decreased until it returned to 25 • C at 6:30 p.m., until repeating the cycle the following day.…”
Section: Experimental Conditions and Experimental Designmentioning
confidence: 99%
“…Treatments consisted of a combination of an aqueous solution of sodium nitroprusside (SNP, NO donor; Na 2 [Fe (CN) 5 NO]•2H 2 O, SigmaAldrich, Saint Louis, MO, USA) and elevated temperature imposed at the V3 development stage [17]. The plants were treated with two doses of SNP: 0 and 100 µM for two consecutive days at 24-h intervals, using a hand sprayer with a total volume of 5 mL per plant [18], under 25 • C and 40 • C. The high temperature (HT) was imposed after the both SNP applications by gradually increasing from 25 • C at 10:00 a.m. until reaching 40 • C ± 0.5 • C at 11:30 a.m., which was maintained for five hours. After this period, the temperature gradually decreased until it returned to 25 • C at 6:30 p.m., until repeating the cycle the following day.…”
Section: Experimental Conditions and Experimental Designmentioning
confidence: 99%
“…The reduction in protein content in Oryza sativa leaves by paraquat was prevented by nitric oxide by reducing the level of malondialdehyde and improving the activity of antioxidant enzymes, such as SOD, POD and GR [79]. Nitric oxide given as sodium nitroprusside at 50, 100 and 200 µM protected Glycine max plants by scavenging the ROS generated by 168 g ha -1 lactofen [80]. The protective role of brassinosteroids against biotic and abiotic stress has been documented in literature, but the action of brassinosteroids against damage by herbicides is not well validated.…”
Section: Newly Added Plant Hormonesmentioning
confidence: 98%
“…Nitric oxide (NO), an endogenous free radical or provided through the donor compounds, such as sodium nitroprusside (SNP), has been studied for its ability to contain the damage caused by the oxidative stress in plants (Ferreira et al, 2011), with its protective action confirmed by the use of the nitric oxide sequestrant cPTIO (Neill et al, 2003).…”
Section: Introductionmentioning
confidence: 99%